A Federal tax program to promote economic stability and growth - Kimmel, Lewis Henry (Washington Brookins Institution, 1960)
Federal tax policy is no longer based on the as sumption that an annually balanced budget is essential. In creasing taxes to maintain budgetary balance during a recession or depression would be construed as a perverse approach to fiscal policy. The built-in stabilizing features of the tax struc ture are regarded favorably by economists, members of Con gress, and government officials. Federal tax policy can be helpful in preventing or controlling inflation. Not all inflation ary situations can be controlled by increases in taxes; marked rises in taxes in themselves have dislocating effects. Sharp changes in federal expenditures have been more important as an inflation-making factor than postwar deficits. The bases for the personal and corporate income taxes should be strength ened. Inclusion of sources of income now excluded and the elimination of various forms of favored treatment would permit appreciable reductions in tax rates.
aia 13/03/2019
Loans
Keywords: Taxation; United states